PEMBERDAYAAN MASYARAKAT MISKIN MELALUI PENDEKATAN MODAL SOSIAL - Mohammad Armoyu (LP2M Universitas Ibrahimy, 2013)
This article discussed the empowerment of the poor through social capital approach. The problem formulation specifically was: (1) How was social capital approach to improve the empowerment of the poor. (2) How is the work done to solve the poverty problem. Its study-perspective was a social science. This research was an overview of poverty in Indonesia. Data were collected and analyzed by describing the use of descriptive analytical models. The results showed: (1) Poverty was a social problem which became more and more complex and complicated. (2) Many attempts were made to solve the problem of poverty, but poverty still persist even showed increasing symptoms, although it was likely reported to decrease. Regardless of how did the statistics presents of poverty reduction, poverty, in fact, became an increasingly worrisome problem. A lot of effort was made, but the poverty was still persist.